واقع حقوق الإنسان في الجزائر زمن الإصلاحات وتفعيلها من خلال آلية اللجنة الوطنية الاستشارية لحماية وترقية حقوق الإنسان - خلفة, نادية (revue mofakir; No 14 (2017): مجلـــة المفكــر, 2018)
The study entiteled « The Reality of Human Rights during the reform time » aims at presenting and explaining the laws of refom which were enacted in 2012 in Algeria. Those laws ,regarding political parties,associations,the media, elections and the enlargement of women’s choices in the »Representative Councils »,emergend during internal as well as external sircomstances(The Arab Uprisings). The main thesis of the study among political analysts and jurists at varios levels is :Whether those laws establish a complementary system of Human Rights or merely a project to calm the situation and absorb the populus angares ?AND CAN THE Algerian NATIONAL Consultative Commission for Promoting and Protecting Human Rights-as a main public institution working in the field of human rights and specialysing protecting and enhancing the respect of those rights,work to ACTIVATE the rights most demanded and which the laws of reform try to specify them ?